Development and in vitro evaluation of extended-release theophylline matrix capsules (Revista Brasileira de Ciências Farmacêuticas, 2007)
Polymers like cellulose (MethocelTM K100MPRCR, K15MPRCR and E4MCR) at different proportions (15-35%) were used to slow the release of theophylline (100 mg) from capsules. Volumetric method for powder filling capsules was used to prepare the capsules. Drug release from capsules was performed using apparatus 1, at 100 rpm and 900 mL of intestinal medium without enzymes (pH 7.5), at 37 °C, following the USP 28th ed. (Test 8). Dissolution profiles were compared to two batches of commercial extended-release capsules. Capsules compounded with 35% (wt/wt) of MethocelTM E4MCR showed dissolution profile according to the official especifications. Similar results were reproduced with other ten compounded batches. Commercial extended-release capsules containing theophylline pellets (100 mg) showed quick drug release when submitted to the same test, indicating that, in these conditions, the capsules did not show prolonged release. Mathematical models like zero-order, first-order and Higuchi were applied in kinetic studies of theophylline release from the compounded capsules. Polymers were efficient to control the release of theophylline in capsules involving diffusion and erosion as mechanisms, and that first-order model was the best fitted one for theophylline matrix capsules. These results support that compounded extended-release capsules can be prepared, since the drug release tests can be done.